2020
DOI: 10.3390/jcs4030105
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Carbon Nanomaterial/Epoxy Resin for Electrically Conductive Adhesives

Abstract: The increasing complexity of printed circuit boards (PCBs) due to miniaturization, increased the density of electronic components, and demanding thermal management during the assembly triggered the research of innovative solder pastes and electrically conductive adhesives (ECAs). Current commercial ECAs are typically based on epoxy matrices with a high load (>60%) of silver particles, generally in the form of microflakes. The present work reports the production of ECAs based on epoxy/carbon nanomaterials us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…While the conductivity will be provided using conductive fillers such as Ag, Ni, graphite, graphene, CNTs etc. [11][12][13]. Various conductive fillers have been studied including zinc complexes [14,15], metal oxide [16] cadmium [17], cobalt nanoparticles [18], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the conductivity will be provided using conductive fillers such as Ag, Ni, graphite, graphene, CNTs etc. [11][12][13]. Various conductive fillers have been studied including zinc complexes [14,15], metal oxide [16] cadmium [17], cobalt nanoparticles [18], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Suherman et al, has reported 28 Scm - 1 Suherman based upon 80% graphite with epoxy [19]. The research group of Duarte and Paulo [12] have studied epoxy resin composites consist of single & multiwalled carbon nanotubes (SWCNT & MWCNT) calculated volume resistivity of about 1×10 1 and 1×10 6 Ω.cm for SWCNT & MWCNT. In another work Dhakate et al [20] have deliberated graphite (natural and synthetic) as the conductive material with epoxy resin for bipolar plates with the highest conductivity of about 150 Scm -1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ], while the conductivity will be provided using conductive fillers such as Ag, Ni, graphite, graphene, CNTs, etc. [ 15 , 16 , 17 ]. Various conductive fillers have been studied, including zinc complexes [ 18 , 19 ], metal oxide [ 20 ], cadmium [ 21 ], cobalt nanoparticles [ 22 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Suherman et al reported a conductivity of about 28 Scm −1 through using about 80% of graphite along with epoxy resin, resulting in improved mechanical and electrical performances of epoxy–graphite composites [ 23 ]. The research group of Duarte and Paulo [ 16 ] studied epoxy resin composites consisting of single- and multiwalled carbon nanotubes (SWCNTs and MWCNTs) and calculated a volume resistivity of about 1 × 10 1 and 1 × 10 6 Ωcm for SWCNTs and MWCNTs. In another work, Dhakate et al [ 24 ] used graphite (natural and synthetic) as the conductive material with epoxy resin for bipolar plates, with the highest conductivity at about 150 Scm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The increase in roughness increases interfacial area, thereby increasing interfacial strength. The other method of increasing interfacial strength is introducing surface functional groups that increase the affinity of epoxy matrix with CF through polar interactions [7][8][9][10][11][12] . Several researchers have worked on analysing the failure of fiber based polymeric composites in terms of interfacial micromechanical approach [13][14][15][16] and spectroscopic characterisation of interfaces.…”
mentioning
confidence: 99%